JENIS-JENIS MOLUSKA (GASTROPODA DAN BIVALVIA) PADA EKOSISTEM MANGROVE DI DESA DEDAP KECAMATAN TASIKPUTRIPUYU KABUPATEN KEPULAUAN MERANTI, RIAU - WAHYUNI, SRI (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aims to determine the diversity of Molusca (Gastropods and Bivalves) contained of mangrove ecosystem in Dedap Village Tasikputripuyu District Meranti Island Regency, Riau. This study was conducted from Oktober 2015 to Januari 2016 by using survey method. Gastropods and Bivalves drawn later identified by describing the diversity of Gastropods and Bivalves are obtained. Results of the study found a 6 family and 14 species for class of Gastropods (Cassidula aurisfelis, Ellobium aurisjudae, Littoraria scabra, L. undolata, Pugilina cochlidium, Chicoreus capucinus, Indothais gradata, Nerita articulata, N. violacea, Cerithidea obtusa, C. quoyii, Cerithideopsilla alata, Cerithidiopsis malayensis and Telescopium telescopium), and 1 family and 1 species for of class Bivalves (Polymesoda bengalensis).